2021
DOI: 10.1371/journal.pone.0250855
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome and type 2 diabetes status in the Multiethnic Cohort

Abstract: Background The gut microbiome may play a role in inflammation associated with type 2 diabetes (T2D) development. This cross-sectional study examined its relation with glycemic status within a subset of the Multiethnic Cohort (MEC) and estimated the association of circulating bacterial endotoxin (measured as plasma lipopolysaccharide-binding protein (LBP)) with T2D, which may be mediated by C-reactive protein (CRP). Methods In 2013–16, cohort members from five ethnic groups completed clinic visits, questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 71 publications
(127 reference statements)
3
31
0
1
Order By: Relevance
“…A study showed that constructed microbiome risk score was consistently associated with T2DM and future glucose increment and was related to a variety of blood metabolites derived from gut microbiome (34). Maskarinec et al demonstrated that T2DM was related to the abundance of some intestinal floras and gut microbiome might cause chronic systemic inflammation and T2DM through bacterial translocation (35). A study showed that microbial-derived or microbial-modified metabolites in serum could predict the risk of T2DM (36).…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that constructed microbiome risk score was consistently associated with T2DM and future glucose increment and was related to a variety of blood metabolites derived from gut microbiome (34). Maskarinec et al demonstrated that T2DM was related to the abundance of some intestinal floras and gut microbiome might cause chronic systemic inflammation and T2DM through bacterial translocation (35). A study showed that microbial-derived or microbial-modified metabolites in serum could predict the risk of T2DM (36).…”
Section: Discussionmentioning
confidence: 99%
“…What is more, SNP rs9927590 (found within WWOX gene) has been reported to be involved in obesity and was associated with a metabolic pathway involved in short-chain fatty acid (SCFA) production [ 124 ]. The gut bacterial production of SCFA may prevent T2D through appetite control and energy homeostasis [ 125 , 126 ]. Additionally, butyrate, one of SCFA, has been displayed to have an influence on gut hypoxia by mitochondrial beta-oxidation and by interacting with HIF1α to maintain tight junctions [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gut bacterial production of SCFA may prevent T2D through appetite control and energy homeostasis [ 125 , 126 ]. Additionally, butyrate, one of SCFA, has been displayed to have an influence on gut hypoxia by mitochondrial beta-oxidation and by interacting with HIF1α to maintain tight junctions [ 125 ]. It has been demonstrated that butyrate metabolism reduces local oxygen level which stabilizes HIF1α [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations